MANAJEMEN PERILAKU BIROKRASI TERHADAP PENINGKATAN PELAYANAN PUBLIK DI KANTOR DESA BULO WATTANG KECAMATAN PANCA RIJANG KABUPATEN SEDENRENG RAPPANG - Supriyadi Kahar; Muhammad Rusdi; Abdul Jabbar (PRAJA: Jurnal Ilmiah Pemerintahan, 2019)
This study aims to determine the management of bureaucratic behavior at the Bulo Wattang Village office, public services at the Bulo Wattang Village office and to determine the management of bureaucratic behavior towards improving public services at the Bulo Wattang Village office in Panca Rijang District, Sidenreng Rappang Regency. The population in this study was 337 heads of households where the sampling used was Probability Sampling, with a random sampling technique using the 10% Yount Formula with a total sample of 34 heads of households. This study used a Quantitative Descriptive Method. Data collection techniques used through observation, questionnaires, and documentation. The data analysis technique used is frequency tabulation analysis, and linear regression analysis using SPSS 16 for Windows. The results of this study show that the average percentage of bureaucratic behavior management in the office of Bulo Wattang Village, Panca Rijang District, Sidenreng Rappang Regency is 65.8% with a good category, public services at the Bulo Wattang Village office, Panca Rijang District, Sidenreng Rappang District are 60.32% with a fairly good category of bureaucratic behavior management to improve public services in the office of the Village of Bulo Wattang, District of Panca Rijang, District of Sidenreng Rappang by 33.0% with an influence category.